Thyroidectomy under local anaesthesia in a poor resource health facility in Northeastern Nigeria - Aliyu S; Ningi AB; Rabi'u MB (Journal of Surgery and Surgical Research - Peertechz Publications, 2020)
Background: The provision of quality health care is one of the priorities of every government. The quality of such care is however, limited by the human and technical resources available. The varying types of thyroidectomy for Goitres are often done under general anaesthesia, unless, there is a contraindication such as, cardiopulmonary instability. Recently, there is increasing evidence that thyroidectomy could be done under local anaesthesia with or without anxiolytics or opioid analgesia augmentation. This study reports on our experience of performing thyroidectomy under infiltrative local anaesthesia. Objectives: To evaluate the safety of performing thyroidectomy under infiltrative local anaesthesia and compare the post-operative outcome with that done under general anaesthesia. Patients and methods: This is a descriptive case series of 59 patients that underwent thyroidectomy under field block with 1% Lignocaine with Adrenaline 1:200,0000 dilutions. Dose was standardised for all patients at 4mg/kg under monitored anaesthesia. The period under study covered from October 2017-October 2019. The patients' characteristics analysed were Biodata, clinical diagnosis, patients' weight, type of surgery, duration of surgery and complications. Results: The study population were 59 patients, 88.1% were females, 11.9% were males with female -male ratio of 8:1. The mean age was 42.03(+_3.5), simple multinodular goitre was the most common subtype 47.5%, toxic multinodular goitre 39%, diffuse simple goitre and diffuse toxic goitre 5.1% each. Malignant goitre 3.4% and all are papillary carcinomas. 54,2% off all the goitres are WHO grade 3. The mean duration of surgery is 40minutes and the average duration of hospital stay is 24-48hours. There were 6 complications. 1(1.7%) sub-cutaneous haematoma, 1(1.7%) post-operative hypocalcaemia, 2(3.4%) keloidal scar and 2(3.4%) surgical site infections. Conclusion: Thyroidectomy under infiltrative local anaesthesia is safe if done by a trained surgeon, in a poor resource health facility. Limitation: Patient's preference for general anaesthesia and short-necked, obese patients.